Seed weight variation of wyoming sagebrush in Northern Nevada - Busso, Carlos Alberto (2005)
Seed size is a crucial plant trait that may potentially affect not only immediate seedling success but also the subsequent generation. We examined variation in seed weight of Wyoming sagebrush (Artemisia tridentata ssp. wyomingensis Beetle and Young), an excellent candidate species for rangeland restoration. The working hypothesis was that a major fraction of spatial and temporal variability in seed size (weight) of Wyoming sagebrush could be explained by variations in mean monthly temperatures and precipitation. Seed collection was conducted at Battle Mountain and Eden Valley sites in northern Nevada, USA, during November of 2002 and 2003. Frequency distributions of seed weight varied from leptokurtic to platykurtic, and from symmetry to skewness to the right for both sites and years. Mean seed weight varied by a factor of 1.4 between locations and years. Mean seed weight was greater (P<0.05) in 2003 than in 2002 at both sites. This can partially be attributed to 55% greater precipitation in 2003 than 2002, since mean monthly temperatures were similar (P>0.05) in all study situations. Simple linear regression showed that monthly precipitation (March to November) explained 85% of the total variation in mean seed weight ( P=0.079). Since the relationship between mean monthly temperature (June-November) and mean seed weight was not significant (r2=0.00, P=0.431), this emphasizes the importance of precipitation as an important determinant of mean seed weight. Our results suggest that the precipitation regime to which the mother plant is exposed can have a significant effect on sizes of seeds produced. Hence, seasonal changes in water availability would tend to alter size distributions of produced offspring.